LittleHelper: An augmented reality glass application to assist individuals with autism in job interview - Qingguo Xu; Cheung, Sen-ching Samson; Soares, Neelkamal (2015 Asia-Pacific Signal and Information Processing Association Annual Summit and Conference (APSIPA), 2015)
With the rapid increase in the prevalence of autism spectrum disorder (ASD) in 1990s, there are approximately 50,000 individuals with ASD turning 18 years old every year. The community-based employment rate, even for those individuals with higher functioning capabilities, is very low. This can be partly explained by socio-communicative skill deficits which are a hallmark of ASD, such as poor eye-contact and inappropriately modulated speech. There has been little work in developing assistive technology to help individuals with ASD to compensate for these deficits. In this paper, we propose a new system based on a wearable augmented-reality glass platform called LittleHelper to provide customized supports for individuals with ASD in enhancing social communication during a job interview. Using the built-in camera and microphone, LittleHelper can detect the position of the interviewer relative to the center of the camera view, and measure the sound level of the user. Based on these inputs, appropriate visual feedbacks are provided back to the user through the optical head-mounted display.